Dampak Kredit Terhadap Pendapatan Usahatani Kopi Arabika - Dharmawan, Sarah Setiasih; Karyani, Tuti (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
Coffee is one of the commodities that have opportunities in agricultural development. One of coffee producing region is in Margamulya, Pangalengan, Bandung with the Java Preanger arabica coffee brand marketed by Margamulya Coffee Producers Cooperative. Java Preanger is sold to domestic and abroad. Coffee production should always be available in large quantities to meet market demand. Production coffee by some farmers is low because it does not do maintenance properly. This is due to the capital coinstrat. Margamulya Coffee Producers Cooperative assist the farmers in using capital in a way to access credit. The purpose of research impact of credit on arabica coffee income. This research used inferential quantitative methods. The analysis was tested by Independent Sample T-Test. Sampling was done by doing Simple Random Sampling methods. The results state that credit provides a significant difference in arabica coffee income for farmers credit recipients and non-credit recipients because their used for arabica coffee farming and for labor wages.